Design and Build a Mobile Bookstore Application in Order to Attract Consumers' Reading Interest Using Prototyping Method - Liyunjira, Liyunjira; Lesman, I Putu Dody Lesmana Dody (Journal of Disruptive Learning Innovation (JODLI), 2022)
Advances in technology today encourage many changes in human life from the information age to the digital era in all fields. Currently, almost all activities can be enjoyed through smartphones. Utilization of technology is one of the innovative steps to attract people's reading interest. This is not the case with e-book applications that already have many versions in development. However, with so many e-book applications that can be downloaded for free or paid for, it is still not an infrastructure to be able to attract people's reading interest which is very concerning. So we need an e-book application that can attract people's reading interest. The purpose of this research is expected to produce an e-book application that is more efficient, economical and provides convenience so that it can attract people's reading interest.The method used in this research is the prototyping method which consists of stages of communication, planning, modeling, prototype formation and deployment and feedback.Based on the results of the study, it shows that this mobile bookstore application can attract users' reading interest. This is evidenced by the results of user responses with an average value of 84%.